Tingkat Konsumsi Energi dan Protein dengan Status Gizi Balita - Dieni Septiawati; Yaktoworo Indriani; Reni Zuraida (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction: Lack of protein-energy or malnutrition is one of the nutritional disorders in the world and Indonesia. Purpose: The purpose was to determine the relationship between the level of energy and protein consumption with the nutritional status of children under five. Method: This research used is observational analytic with a cross-sectional approach. The research was conducted in December 2020. The sampling technique used a total sampling of 81 toddlers. Data collection tools using questionnaires and observation sheets. Data analysis used the Spearman Rank correlation test. Result: Most toddlers have energy and protein consumption in good category and nutritional status is normal. Conclusion: There is a relationship between energy and protein consumption with the nutritional status of children under five. The community can pay more attention to the food consumed by toddlers so that it can improve the health status of children.